Model Strategi Komunikasi Berbasis Kompetensi Sosial Guru Pendidikan Anak Usia Dini dalam Memperkuat Kemitraan Stakeholder - Ratna Wahyu Pusari; Coryza Nursyahbani; Yusuf Setya Wardana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the dynamics of early childhood education teachers’ social competencies in communication practices, identify the communication strategies employed, examine communication barriers, and formulate a social competence-based communication strategy model to strengthen stakeholder partnerships. The study employed a qualitative approach with a case study design. The research subjects were selected through purposive sampling and consisted of 12 teachers, 3 school principals, and 6 parents or school committee members in Grobogan Regency, Central Java, Indonesia. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed thematically using an interactive model. The results indicate that teachers’ social competencies are dynamic, particularly in terms of interpersonal adaptability, empathy development, and the use of digital communication in interactions with stakeholders; however, these competencies have not yet been systematically integrated into structured communication strategies. Communication practices tend to develop adaptively but remain dominated by one-way, informative communication patterns. Communication barriers are multidimensional, encompassing individual, social, and structural factors. This study produced a social competence-based communication strategy model that emphasizes dialogic, empathetic, and collaborative communication in building stakeholder partnerships. The originality of this study lies in the integration of social competence and communication strategies into a single empirically grounded conceptual model. Theoretically, this study contributes to stakeholder-based educational communication research, while practically providing guidance for early childhood education teachers in developing more effective and collaborative communication practices.